Penerapan Kontrol Kualitas Produk Roti (Bread) di Pastry Section Harris Hotel & Conventions Bundaran Satelit Surabaya - Cindi Fatikha Maulidia; Niken Purwidiani; Lilis Sulandari; Nugrahani Astuti (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to gain an in-depth understanding of the implementation of bread product quality control in the Pastry Section of Harris Hotel & Conventions Bundaran Satelit Surabaya, covering four main aspects: raw materials, production process, storage, and presentation. Furthermore, this study focuses on understanding the Standard Operating Procedures (SOPs) for bread production operations and the level of implementation of these SOPs in daily work practices. The research method used is descriptive qualitative, with data collection techniques through direct field observation, interviews with pastry section staff, and documentation related to bread production activities. The results show that bread product quality control is carried out comprehensively. In the initial stage, raw material selection is carried out strictly to ensure quality, freshness, and food safety. The production process is carried out according to standard procedures, paying attention to equipment cleanliness, processing techniques, and timeliness, resulting in products that are consistent in taste and texture. The storage stage is also carried out hygienically with a system for arranging ingredients and finished products that pay attention to temperature, humidity, and cleanliness of the storage room. In the final stage, bread is served with good aesthetic standards while maintaining food safety aspects, thus adding value to the hotel guest experience. The bread production operational SOP has been systematically developed and serves as an important reference for all pastry section employees in carrying out their daily tasks. Employee compliance with the SOP is high, although challenges remain, such as limited trainee skills and delays in raw material supplies from suppliers. These challenges can usually be overcome through direct supervision, internal training, and good communication with material suppliers. Overall, the implementation of quality control and bread production SOPs at Harris Hotel & Conventions Bundaran Satelit Surabaya has been running smoothly and consistently.